Predictors of Tuberculosis Treatment Default in Pulmonary - Khalid Mehmood , Inaam Qadir Javed Hashmi , Javed Akhtar Rathore , Muhammad Luqman Satti, Khadeeja Tul Kubra Hashmi , Shizza Khalid , Abdur Rahman Hashmi, Khalid Mehmood , Inaam Qadir Javed Hashmi , Javed Akhtar Rathore , Muhammad Luqman Satti, Khadeeja Tul Kubra Hashmi , Shizza Khalid , Abdur Rahman Hashmi (Journal of Rawalpindi Medical College, 2017)
To detect the predictors of treatment defaults in Pulmonary Tuberculosis (PTB) and Extra Pulmonary Tuberculosis (EPTB). Methods: In this cross sectional study 140 adults, with diagnosis of pulmonary tuberculosis (PTB) and extra pulmonary tuberculosis ( EPTB), with treatment defaults, were included . The study protocol incorporated demographic, clinical characteristics of patients, structured questionnaire, physical examinations, radiological, laboratory investigations and relevant predictors for TB treatment defaults. The statistical analysis was performed using SPSS 20. Results: Mean age of study group was 42.3±20.3. Majority (67.1%) were male. Ninety four (67.1%) had PTB and 46 (32.9%) had EPTB. Factors identified to be associated with TB treatment default were male gender ,distance from the health post, displacement, financial constraints, no body at home to bring medicine or take patients to hospital, routes closed in winters, subjective improvement of symptoms and travelling /shifting to other place. Conclusions: Treatment default is seen in pulmonary and extra pulmonary tuberculosis. Due to lack of uniform diagnostic and therapeutic strategy in EPTB treatment, most physicians treat on clinical symptoms for a prolonged duration of 12 to 24 months.